2009
DOI: 10.3354/dao02034
|View full text |Cite
|
Sign up to set email alerts
|

In vivo exposure of susceptible and non-susceptible fish species to Myxobolus cerebralis actinospores reveals non-specific invasion behaviour

Abstract: In vivo exposure of susceptible and non-susceptible fish species to Myxobolus cerebralis actinospores reveals non-specific invasion behaviour

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 18 publications
(22 reference statements)
2
34
1
Order By: Relevance
“…Actinospores attach to the fish by firing their polar filaments, allowing the vegetative sporoplasm to penetrate (El-Matbouli et al, 1995). Portals of entry for M. cerebralis include the skin, fins, buccal cavity, digestive tract and gills (Antonio et al, 1998; El-Matbouli et al, 1999; Kallert et al, 2009; Markiw, 1989). Mucosal tissues also represent a primary invasion route for other myxozoans (Table 1).…”
Section: Biology Of Myxozoansmentioning
confidence: 99%
See 1 more Smart Citation
“…Actinospores attach to the fish by firing their polar filaments, allowing the vegetative sporoplasm to penetrate (El-Matbouli et al, 1995). Portals of entry for M. cerebralis include the skin, fins, buccal cavity, digestive tract and gills (Antonio et al, 1998; El-Matbouli et al, 1999; Kallert et al, 2009; Markiw, 1989). Mucosal tissues also represent a primary invasion route for other myxozoans (Table 1).…”
Section: Biology Of Myxozoansmentioning
confidence: 99%
“…During the invasion process, the three polar filaments anchor the parasite to the fish, facilitating the emergence of the ameboid sporoplasm from between the valve shells and its entry into the fish through the secretion opening of a mucus pore (El-Matbouli et al, 1999; Kallert et al, 2007). These initial steps are not host specific, and may occur on contact with any fish species (Kallert et al, 2009), but successful infection only occurs in salmonids. Once in the fish, the sporoplasm begins an asexual replicative phase (presporogonic phase) and at the same time begins to migrate through the epidermis and peripheral nerves to the cartilage (El-Matbouli et al, 1995; El-Matbouli et al, 1999).…”
Section: Biology Of Myxozoansmentioning
confidence: 99%
“…In contrast, actinospores of Myxobolus cerebralis did not react to fish mucus alone (El-Matbouli et al, 1999b) and required both mechanical and chemical stimuli (Kallert et al, 2005). Nevertheless, M. cerebralis actinospores were unable to specifically detect susceptible fish (salmonids), but also penetrated gills of carp at the same rate as gills of trout (Kallert et al, 2009). Further, Kallert et al (2007) revealed the process of host invasion of M. cerebralis actinospores in detail; immediately after filament discharge of actinospores, contraction of the filaments brings the actinospore apex to contact with the host surface.…”
Section: Invasion Mechanismsmentioning
confidence: 99%
“…The same was shown experimentally for M. cerebralis by preincubation of carp with actinospores of the parasite. Thereby, infection rate in susceptible rainow trout was reduced significantly (Kallert et al, 2009). …”
Section: Removal Of Actinosporesmentioning
confidence: 99%
“…An alternate outcome is that the native parasite infects the exotic host but does not develop transmissible spores, thus the exotic host acts as a sink for native parasites and may provide relief for indigenous hosts (Tompkins and Poulin 2006;Poulin et al 2010). Although this process has not been reported for myxozoans, laboratory experiments support the concept: M. cerebralis actinospores can attach to carp-an unsuitable host-thereby decreasing available infectious stages and reducing the subsequent myxospore load in compatible trout (Kallert et al 2009 …”
Section: Modes Of Myxozoan Introduction Dispersal and Amplificationmentioning
confidence: 52%